Energy Politics in the MENA Region From Hydrocarbons to Renewables? - Talbot, Valeria (ISPI Publications, 2022)
The war in Ukraine has highlighted Europe's urgency to diversify its energy supplies and reduce dependence on Russia. While, in such context, energy security has become a top political priority for Europe, energy resources from the Middle East and North Africa (MENA) region have drawn European countries' renewed attention. Boasting abundant oil and gas reserves, the MENA region will likely play a leading role in Europe's current energy crisis. While MENA exporters' ability to increase their supply is limited in the short-term, more resources are likely to be available in a longer-term perspective. As Europeans are scrambling for alternatives, this Report analyses the different implications for a number of MENA exporters of fossil fuels. As these countries have become even more central to Europe's energy security, assessing their prospects is of paramount importance, including not only their short-term role as suppliers of fossil fuels, but also their opportunity to accelerate along the path of the green transition. How is the current energy crisis affecting the role of MENA hydrocarbons producers as Europe's energy suppliers? How will Europe's needs in additional resources redefine energy geopolitics in the Middle East and North Africa? Which new prospects for their green transition?